The Effectiveness of Conventional Marketing Strategy Toward a Sustainability of Indonesian Tourism: A Systematic Review and Meta-Analysis - Manao, Alwinda; Hurriyati, Ratih; ., Disman; Aziz, Fathul; Prayuda, Uud; Berlianne, Jelsi Ratu; Ganesha, Andi Hendra Putra; Bahtiar, Jessica Yunanda; Laduri, Lavena (Journal of Posthumanism, 2025)
This study presents a systematic review using meta-analysis to examine the effect of conventional marketing strategies on the sustainability of Indonesian tourism. Thirty-two empirical studies were analyzed to estimate the overall effect size and test the influence of moderating factors such as destination image, media exposure, regional development level, and tourist type. The meta-analysis revealed a strong and significant positive effect of conventional marketing on tourism sustainability, with an estimated Hedge’s g effect size of 1.136 (p < 0.05). Subgroup analysis showed that destination image, regional development level, and tourist type significantly moderated the effect, while media exposure did not. The findings highlight the continued relevance of traditional marketing tools in promoting sustainable tourism, especially in regions with positive destination image and advanced development. The study offers theoretical contributions to tourism and marketing literature by reinforcing classical models such as AIDA and contingency theory. Practical implications suggest that tourism stakeholders should adopt tailored conventional marketing strategies that reflect local contexts and tourist profiles. Limitations related to study selection, moderator range, and methodological diversity are acknowledged. This study is the first to conduct a meta-analytic review focused on conventional marketing’s role in sustaining Indonesian tourism, offering novel insights and a foundation for future research.